0411 Exposure to diesel engine exhaust and the risk of als. (21st August 2017) - Peters, Susan; Ge, Calvin; Veldink, Jan; Berg, Leonard van den; Vermeulen, Roel
Abstract : Background: Only few risk factors have been identified for amyotrophic lateral sclerosis (ALS). Higher risks were reported for various occupations (e.g. farmers, construction workers), but responsible exposures remain largely unknown. We investigated the association between occupational exposure to diesel engine exhaust and sporadic ALS in a population-based study with detailed information on possible confounders. Methods: An ongoing ALS case-control study is being conducted in the Netherlands since 2006, and we here present data for 2006–2014. Lifetime occupational histories and lifestyle factors were collected via questionnaires. A general population job-exposure matrix was assigned to estimate exposure to diesel engine exhaust. All exposure variables were estimated up to two years before survey to account for any changes due to disease onset. Odds ratios were estimated by logistic regression models, adjusted for age, sex, smoking and alcohol. Results: Data were available for 1040 sporadic ALS cases (63.6% male) and 2050 controls (60.2% male). Ever occupational exposure to diesel engine exhaust was not associated with risk of ALS (OR=1.06, 95% CI 0.87–1.28). No exposure-response relation was observed for either cumulative exposure or exposure duration on a continuous scale. Conclusion: Our analysis suggests that exposure to diesel engine exhaust is not associated with an increased risk of ALS.